Carbon Tax, Environmental Costs, and Green Investment on the Profitability of Mineral and Coal Companies - Rendi Herdiyanto; Moh Yudi Mahadianto; Mardi Mardi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to determine the influence of carbon taxes, environmental costs, and green investments on the Sprofitability of Mineral and Mineral companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2024. Applying a descriptive quantitative approach through purposive sampling techniques, this study processed 40 observational data using multiple linear regression analysis. The research findings show varied results and provide strategic insights. First, the Carbon Tax has proven to have no significant influence on profitability, considering that its implementation in Indonesia is still in the form of regulatory discourse (price shadow) so that it has not burdened the company's cash flow in real terms. Second, Environmental Costs have a significant positive effect on profitability, which confirms the validity of the Legitimacy Theory where environmental spending is able to strengthen public trust and operational stability.